1985
DOI: 10.1172/jci111864
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile growth hormone secretion in normal man during a continuous 24-hour infusion of human growth hormone releasing factor (1-40). Evidence for intermittent somatostatin secretion.

Abstract: Growth hormone (GH) secretory patterns were studied in a patient with ectopic growth hormone releasing factor (GRF) secretion and in normal men given continuous infusions of human growth hormone releasing factor (1-40)-OH (hGRF-40). In the patient with ectopic GRF secretion, GH secretion was pulsatile despite continuously elevated immunoreactive GRF levels. To determine if pulsatile GH secretion is maintained in normal subjects, we administered to six healthy young men vehicle or hGRF-40, 2 ng/kg per min, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
75
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(83 citation statements)
references
References 23 publications
7
75
1
Order By: Relevance
“…Such diurnal variations during an unchanging GHRH stimulus suggest to us (but do not prove) concomitant 24-h non-uniformity in the release of somatostatin and/or co-secretagogues of GH. These considerations would also explain ongoing pulsatile GH release during continuous GHRH infusions (40). Since the amplitude and mesor (but not the acrophase) of the 24-h rhythm in GH secretory burst mass increased (by 2.5-and 3.5-fold respectively) during GHRH infusion, we infer that the magnitude but not the timing of daynight GH rhythmicity is modulated by GHRH.…”
Section: Discussionmentioning
confidence: 82%
“…Such diurnal variations during an unchanging GHRH stimulus suggest to us (but do not prove) concomitant 24-h non-uniformity in the release of somatostatin and/or co-secretagogues of GH. These considerations would also explain ongoing pulsatile GH release during continuous GHRH infusions (40). Since the amplitude and mesor (but not the acrophase) of the 24-h rhythm in GH secretory burst mass increased (by 2.5-and 3.5-fold respectively) during GHRH infusion, we infer that the magnitude but not the timing of daynight GH rhythmicity is modulated by GHRH.…”
Section: Discussionmentioning
confidence: 82%
“…IGF-I administration in this syndrome diminishes GH secretion, indicating that feedback can be restored (28). The amplified GH secretion is likely mediated by increased hypothalamic GHRH output, while somatostatin release is not affected in view of the unchanged GH pulsatility (29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 89%
“…Measurement of GHRH levels during dynamic tests other than in the basal state has no diagnostic utility, but it may give some insight into the inter-relationship between GHRH and GH secretion in man. Vance et al (1985) found a significant correlation between GHRH and GH levels during a 24 h profile study in a patient with the ectopic GHRH syndrome. We also detected a significant correlation between the two hormones in two different patients with the ectopic GHRH syndrome (Losa et al, 1993), even though the study period was much shorter (8 h).…”
Section: Laboratory Findingsmentioning
confidence: 79%
“…Analysis of GH pulsatility and circadian rhythm has been performed rarely in patients with ectopic GHRH syndrome. When frequent blood sampling was performed, a clear pulsatility of GH levels was detected (Wilson et al, 1984;Vance et al, 1985), whereas lack of pulsatility was reported in two other patients, although both studies had a less frequent pattern of blood sampling (Ch'ng et al, 1985;Barkan et al, 1986). Loss of circadian rhythmicity was suggested in three patients who did not show any nocturnal GH surge (Ch'ng et al, 1985;Vance et al, 1985;Yamasaki et al, 1988b).…”
Section: Laboratory Findingsmentioning
confidence: 99%